Engagement in Music-Related Activities During the COVID-19 Pandemic as a Mirror of Individual Differences in Musical Reward and Coping Strategies - Ferreri, Laura; Singer, Neomi; McPhee, Michael; Ripollés, Pablo; Zatorre, Robert J.; Mas-Herrero, Ernest (Frontiers in Psychology, 2021)
The COVID-19 pandemic and the measures taken to mitigate its impact (e.g., confinement orders) have affected people’s lives in profound ways that would have been unimagable only months before the pandemic began. Media reports from the height of the pandemic’s initial international surge frequently highlighted that many people were engaging in music-related activities (from singing and dancing to playing music from balconies and attending virtual concerts) to help them cope with the strain of the pandemic. Our first goal in this study was to investigate changes in music-related habits due to the pandemic. We also investigated whether engagement in distinct music-related activities (singing, listening, dancing, etc.) was associated with individual differences in musical reward, music perception, musical training, or emotional regulation strategies. To do so, we collected detailed (~1 hour-long) surveys during the initial peak of shelter-in-place order implementation (May-June 2020) from over a thousand individuals across different Countries in which the pandemic was especially devastating at that time: the USA, Spain, and Italy. Our findings indicate that, on average, people spent more time in music-related activities while under confinement than they had before the pandemic. Notably, this change in behavior was dependent on individual differences in music reward sensitivity, and in emotional regulation strategies. Finally, the type of musical activity with which individuals engaged was further associated with the degree to which they used music as a way to regulate stress, to address the lack of social interaction (especially the individuals more concerned about the risk of contracting the virus), or to cheer themselves up (especially those who were more worried about the pandemic consequences). Identifying which music-related activities have been particularly sought for by the population as a means for coping with such heightened uncertainty and stress, and understanding the individual differences that underlie said propensities are crucial to implementing personalized music-based interventions that aim to reduce stress, anxiety, and depression symptoms.